PENGARUH PENGGUNAAN E-WALLET SHOPEEPAY PADA APLIKASI BELANJA ONLINE DAN UANG SAKU TERHADAP PERILAKU MENABUNG SISWA/I SMKN 25 JAKARTA - Putri, Wahyuni Ahmar; Listiorini, Dewi; Mahroji, Dwi (Journal MISSY (Management and Business Strategy), 2025)
This study aims to determine the effect of the use of Shopeepay e-wallet on online shopping applications and pocket money on the saving behavior of students at SMK Negeri 25 Jakarta. This study uses a quantitative approach, and the sample used is 65 students who use Shopeepay e-wallet from the population of 11th grade students majoring in AKL, MPLB, and BDP in the 2024/2025 academic year. This study uses primary data obtained from questionnaire answers and secondary data. All of this is done with SPSS 23 calculations, that there is a significant partial effect of the use of e-wallet on online shopping applications on students' saving behavior can be seen from the calculated t of 3.642> and the t table is 1.999. Pocket money has a significant effect on students' saving behavior, this is indicated by the results of the t test where the calculated t is 5.984> and the t table is 1.999. Based on the results of the SPSS 23 output, the results of the study on the effect of using the Shopeepay e-wallet on online shopping applications and pocket money on students' saving behavior simultaneously have a significant impact, as shown by the results of the F test with a calculated F value > F table (48.762 > 3.14). The independent variables in this study can explain the dependent variable by 61.1% and the rest is influenced by other components not included in the study. Keywords : E-wallet, Pocket Money, Saving Behavior.